Gastric Perforation with Omental Patch Repair: A Rare Complication of Pulmonary Resuscitation in COVID-19 Pneumonia. (11th November 2020) - Marcucci, Vincent; Bhattacharyya, Ratul; Yee, Stephanie; Zuberi, Jamshed; Ingram, Mark
Abstract : A 71-year-old male, diagnosed with coronavirus disease 2019 (COVID-19), was admitted to the medical-surgical floor for supportive treatment. The patient received bag-mask ventilation (BMV) secondary to severe hypoxia and reendotracheal intubation in the hospital on day eleven. A chest X-ray following reintubation noted concern for intra-abdominal air. Significant abdominal distention and subsequent diagnostic imaging showed pneumoperitoneum and a possible perforation of the stomach. The patient underwent an exploratory laparotomy with omental patching for a gastric perforation. Amidst the height of the COVID-19 pandemic, several important findings have been made through the disease sequelae of this individual patient.